Financial Feasibility and Sensitivity of Banana Chips Agroindustry in South Sulawesi - Zulkifli Zulkifli; Besse Dahliana; Suhartina Suhartina (Institut Pertanian Bogor, 2026)
The purpose of this study was to assess the financial feasibility and sensitivity of the banana chips agroindustry at Mappadeceng MSME in Bone Regency, South Sulawesi. The research was conducted in June 2024 using a case study approach based on primary and secondary data. Financial feasibility was analyzed using Net Present Value (NPV), Internal Rate of Return (IRR), Gross Benefit-Cost Ratio (B/C), Net Benefit-Cost Ratio (Net B/C), and Payback Period (PP), followed by sensitivity analysis under adverse business scenarios. The results show that the enterprise is financially feasible, with an NPV of IDR 178,750,000, IRR of 37%, Gross B/C of 1.21, Net B/C of 2.85, and a Payback Period of 6 years and 8 months. The IRR exceeds the prevailing bank interest rate of 10%, indicating strong investment attractiveness. Sensitivity analysis reveals that the business remains feasible under a 15% decrease in sales volume and a 20% increase in raw material prices. However, a 10% reduction in selling price causes the IRR to fall below the benchmark and the B/C ratio to drop below 1, indicating financial vulnerability to price competition. These findings demonstrate that the banana chips agroindustry has solid financial potential but requires effective pricing strategies to maintain long-term sustainability. Keywords: agroindustry, banana chips, financial feasibility, MSMEs, sensitivity